QUR’ANIC INTERPRETATION OF ENVIRONMENTAL LOVE: RECONSTRUCTING ECOLOGICAL VALUES FOR ISLAMIC EDUCATION CURRICULUM - Ulyan Nasri; Husnawadi; M. Gufran; Nasirin; Nurdiah; M. Mizanul Haq; Husnul Haetami; Faruq Abdul Qudus (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
Environmental degradation is not merely an ecological problem but also a moral, spiritual, and educational challenge that requires a value-based response. The Qur’an contains a range of verses that construct an ethical relationship between humans and the natural world, emphasizing stewardship, balance, responsibility, and the prohibition of environmental destruction. This study aims to interpret Qur’anic verses related to environmental love and reconstruct their ecological values as a foundation for developing an Islamic education curriculum. This study employs a qualitative library research method using thematic Qur’anic interpretation (tafsir maudhu’i). Data were collected from relevant Qur’anic verses, classical and contemporary tafsir works, Islamic ecological thought, and literature on Islamic education and curriculum development. The data were analyzed through identification, classification, contextual interpretation, synthesis, and conceptual reconstruction. The study finds that Qur’anic environmental ethics can be reconstructed into five interconnected values: ecological responsibility, compassion toward creation, environmental justice, moderation in resource utilization, and preservation of ecological balance. These values demonstrate that environmental love in the Qur’anic perspective is not merely an emotional attitude but a form of ethical and spiritual responsibility. Their integration into the Islamic education curriculum can strengthen students’ ecological awareness by connecting faith, morality, knowledge, and environmental action. The study contributes a Qur’an-based ecological value framework for developing an Islamic education curriculum that is responsive to contemporary environmental challenges and oriented toward sustainable human–nature relations.